Construction and Validation of the Contextual Victimization Questionnaire (CVCV) with Mexican Young Adults - Gurrola-Peña, Gloria Margarita (2018)
The object of this study was to design and validate a CVCV (Contextual Victimization by Community Violence) questionnaire, with the goal of identifying the frequency at which young adults have been contextual victims of crimes committed in the areas closest to their homes (neighborhood, recreational areas and school). Two groups of university students participated in this study: the first composed of 2,289 youths for the design and exploration of the factor structure of the questionnaire, and the second of 1,507 to confirm the factor structure and the goodness of fit of the model. The results indicate good psychometric properties for the items and for the questionnaire in general, as well as appropriate levels of reliability and validity.